Effects of mental fatigue on endurance performance in the heat - Van Cutsem, J.; De Pauw, K.; Buyse, L.; Marcora, S.; Meeusen, R.; Roelands, B. (Medicine & Science in Sports & Exercise, 2017)
PURPOSE: Mental fatigue is a psychobiological state caused by prolonged periods of demanding cognitive activity and has been observed to decrease time trial (TT) endurance performance by ~3.5% in normal ambient temperatures. Recently, it has been suggested that heat may augment the negative effect of mental fatigue on cognitive performance, raising the question whether it may also amplify the effect of mental fatigue on TT performance.